TINGKAT KECEMASAN TERHADAP KETERAMPILAN BERMAIN SEPAK BOLA SEBELUM BERTANDING PADA ATLET SEPAK BOLA PS SIAK - Fikri, Khoirul; Juita, Ardiah; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstrak : This research is a descriptive study which aims to determine the level ofanxiety regarding soccer playing skills before competing against Ps Siak soccerathletes. The population in this study was the Ps Siak Football Team, totaling 25people, the sampling technique used total sampling. The data collection techniqueused in this research was a questionnaire. From the research process to dataprocessing which began with distributing questionnaires to 25 samples, namely PSSiak Football Athletes, produced data which was used as a benchmark for discussingresearch results with a percentage of 44.88%. Key Words : Level of Anxiety About Skills